Continuous-wave measurement of the hydrogen 1S-2S transition frequency. - McIntyre, D; Beausoleil, R; Foot, C; Hildum, E; Couillaud, B; Hänsch, T (1989)
We have measured the 1S-2S transition frequency in atomic hydrogen with a precision of 7 parts in 1010 by continuous-wave Doppler-free two-photon spectroscopy. We employ cavity-enhanced multimilliwatt radiation near 243 nm produced by sum-frequency generation, and we observe the 1S-2S transition in a low-pressure hydrogen-helium cell with a resolution of 3 parts in 109. For a frequency comparison we detect an optical heterodyne signal at the difference frequency between the 243-nm light used to excite the 1S-2S transition and the second harmonic of a reference laser locked to an interferometrically calibrated Te2130 absorption line near 486 nm. After determining systematic corrections due to the pressure shift of the F=1 hyperfine component in a 0.7 vol. % hydrogen 99.3 vol. % helium gaseous mixture, we obtain the energy-level separation f(1S-2S) =2 466 061 413.2(18) MHz. Choosing a value of the Rydberg constant measured independently by high-resolution spectroscopy of the hydrogen Balmer- transition, we find the hydrogen ground-state Lamb shift to be fLS(1S)=8173.9(19) MHz, in good agreement with the theoretical value of 8172.89(9) MHz. © 1989 The American Physical Society.